1999
DOI: 10.1002/hep.510290346
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor β1induces the expression of α1(i) procollagen mRNA by a hydrogen peroxide-C/EBPβ-dependent mechanism in rat hepatic stellate cells

Abstract: Oxidative stress plays a key role in liver fibrosis. Both inflammatory cells and activated Kupffer cells produce H2O2, an oxidant involved in the activation of hepatic stellate cells (HSC). Increased production of reactive oxygen intermediates (ROIs) in fibrotic livers is associated in part with the up-regulation of transforming growth factor beta (TGF-beta), and this cytokine enhances collagen production by cultured HSC. However, the possible link between oxidative stress and the molecular mechanisms by which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
183
1
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 233 publications
(202 citation statements)
references
References 59 publications
15
183
1
3
Order By: Relevance
“…Of particular interest is the interaction between TGF- and ROS formation. In cultured HSCs, TGF- increases the production of hydrogen peroxide [32], which in turn induces the expression of 1(I) procolagen mRNA [33,34]. The direct profibrogenic effect of hydrogen peroxide has also been observed in co-cultures of HSCs with HepG2 cells overexpressing CYP2E1 [35].…”
Section: Discussionmentioning
confidence: 97%
“…Of particular interest is the interaction between TGF- and ROS formation. In cultured HSCs, TGF- increases the production of hydrogen peroxide [32], which in turn induces the expression of 1(I) procolagen mRNA [33,34]. The direct profibrogenic effect of hydrogen peroxide has also been observed in co-cultures of HSCs with HepG2 cells overexpressing CYP2E1 [35].…”
Section: Discussionmentioning
confidence: 97%
“…Reporter plasmids used in this study, driven by the sequences Ϫ412 to ϩ110 (Ϫ412col1a1CAT), Ϫ378 to ϩ110 (Ϫ378col1a1CAT), Ϫ345 to ϩ110 (Ϫ345col1a1CAT), and Ϫ220 to ϩ110 (Ϫ220col1a1CAT) of the mouse col1a1 gene have been described previously. 15,19 Integrity and orientation of these constructs were verified by DNA sequencing. HSC were cotransfected with 15 µg of each construct plus 3 µg of a luciferase control plasmid, pGL3-Basic (Promega, Madison, WI), using the calcium phosphate method.…”
Section: Methodsmentioning
confidence: 99%
“…15 We showed that TGF-␤ 1 induces the activation and binding to the TbRE of a protein complex that contains C/EBP␤, and demonstrated that H 2 O 2 acts as a second messenger of TGF-␤ 1 -mediated col1a1 gene up-regulation. 15 Because TNF-␣ is known to antagonize TGF-␤ 1 -mediated actions, 16 we considered it important to investigate whether the col1a1 TbRE plays any role in TNF-␣-mediated col1a1 down-regulation. In this article, we report that the TNF-␣-responsive element (TaRE) of the col1a1 gene colocalizes with the TbRE.…”
mentioning
confidence: 88%
“…These cells, when activated, produce and secrete cytokines; cytokines may be proinflammatory, such as TNF-a and IL-1, or profibrotic, such as TGF-b. These proteins can further increase ROS and play important roles in the mediation of hepatic injury [23,[85][86][87], such as fatty liver, by inhibiting lipase of lipoprotein and adiponectin and fibrosis as a result of HSC activation [88][89][90].…”
Section: Viral Hepatitis and Free Radicalsmentioning
confidence: 99%